2010
DOI: 10.4322/apa.2014.035
|View full text |Cite
|
Sign up to set email alerts
|

Plankton structure a in shallow coastal zone at Admiralty Bay, King George Island West ­Antarctic Peninsula (WAP): composition of ­phytoplankton and influence of benthic ­diatoms

Abstract: The phytoplankton composition and biomass are being monitored in Admiralty Bay, Antarctic Peninsula since 2002 to detect possible interannual changes on a long-term monitoring perspective. In this report, we present the results of the 2009/2010 monitoring program regarding the phytoplankton composition during the PROANTAR XVIII operation. The community was dominated by both planktonic and benthic diatoms. A total of 140 species were found, many of them awaiting further morphological studies to determine their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…and Prorocentrum spp.) (Kopczyńska, 2008;Tenenbaum et al, 2010;Lange et al, 2014Lange et al, , 2018 this study) indicates a change in phytoplankton species composition (Lange et al, 2018). This supports the findings of other studies in AB (Sector 1) and King George Island (sector 2), that highlighted shifts in biota due to environmental changes (increase in solar radiation and temperature, thus increasing the sea ice melting) (Kopczyńska, 2008;Schloss et al, 2012;Campos et al, 2013;Mendes et al, 2013Mendes et al, , 2018Saba et al, 2014;Schofield et al, 2017).…”
Section: The Relationship Between Microphytoplankton Community Structsupporting
confidence: 86%
See 2 more Smart Citations
“…and Prorocentrum spp.) (Kopczyńska, 2008;Tenenbaum et al, 2010;Lange et al, 2014Lange et al, , 2018 this study) indicates a change in phytoplankton species composition (Lange et al, 2018). This supports the findings of other studies in AB (Sector 1) and King George Island (sector 2), that highlighted shifts in biota due to environmental changes (increase in solar radiation and temperature, thus increasing the sea ice melting) (Kopczyńska, 2008;Schloss et al, 2012;Campos et al, 2013;Mendes et al, 2013Mendes et al, , 2018Saba et al, 2014;Schofield et al, 2017).…”
Section: The Relationship Between Microphytoplankton Community Structsupporting
confidence: 86%
“…Salinity exhibited little variation, with values higher than 34.0, except at the end of summer 2014-2015 when average values were lower, as observed in the literature both for AB (sector 1) and King George Island (sector 2) (Lange et al, 2018). Lange et al (2014) observed higher salinities during the beginning than at the end of the summer, while Tenenbaum et al (2010) reported reduced salinity for neritic regions, possibly due to the presence of glaciers in the region. In this context, Mendes et al (2018) found lower values for salinity (mean 33.68) in areas near ice-covered regions and higher values (mean 34.14) in regions with little or no influence of ice cover seasonality for sector 7 (Weddel-Scotia Confluence Zone), thus correlating low salinity with water column stability.…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Cosupporting
confidence: 58%
See 1 more Smart Citation
“…Based on these facts since 2009 new approaches to phytoplankton monitoring have been established, including the analysis of size-fractioned pigments by spectro uorometry, and the analysis of density and biovolume of pico-and ultraplankton by epi uorescence microscopy, and furthermore through a higher sampling frequency e ort (Tenenbaum et al, 2011a). Additionally, the composition of microphytobenthos species will be carried out to study the e ects of environmental changes on this community in the nearshore Antarctic ecosystem (Tenenbaum et al, 2011b). In the present study we show the results from early summer obtained during the OPERANTAR XXIX, December 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the composition of microphytobenthos species has been carried out to study the effects of environmental changes on this community in the nearshore Antarctic ecosystem (Tenenbaum et al, 2011b). samples) (Tenório et al, 2011).…”
Section: Introductionmentioning
confidence: 99%